PENGARUH DESAIN VISUAL TERHADAP MINAT BELI GENERASI Z PADA BRAND TIMEPHORIA - Putri Andreas Tuti; Sherena Wahyutari (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Visual design is a crucial element in increasing consumer interest in products, including for the cosmetic brand TimePhoria. This study is intended to investigate the impact of visual design on the purchase intention of Generation Z consumers residing in the Solo Raya area with a minimum age of 17 years. The research approach is based on a quantitative method with simple linear regression analysis. Data acquisition was conducted by means of the distribution of questionnaires to 75 participants included in the Generation Z group. The findings of this study indicate that visual design contributes significantly to purchase intention. The coefficient of determination ($R^2$) parameter of 0.323 indicates that visual design is able to interpret 32.3% of the changes in purchase intention, while the residuals 67.7% is accounted by additional determinants omitted from the current analysis. This empirical evidence shows that attractive visual design that resonates with consumer characteristics can increase purchase intention toward TimePhoria products. The research is projected to function as a practical reference for business actors in developing visual design-based marketing strategies to encourage consumer purchasing decisions.